BEYOND GROWTH METRICS : THE SARONG INDEX AND UNGKU AZIZ’S HUMAN-CENTRED DEVELOPMENT PERSPECTIVE IN MALAYSIA - Muhammad Suhaimi; Fuadah Johari (International Conference on Humanity Education and Society (ICHES), 2026)
In the past, developmental evaluations have been done in Malaysia on the basis of growth centric measurements and have thus often overlooked the real socio-human situation. This paper attempts to review Sarong Index, a groundbreaking account of the concept of development based on humanity in the Malaysian context by Ungku Aziz. Using a qualitative interpretative approach to the corpus of writings of Ungku Aziz and a contemplative evaluation of his policy propositions, the paper clarifies the functional aspects of the Sarong Index as a socio economic indicator that is able to predict poverty and dignity, and the material aspects that define daily life realities, rather than just a rise in aggregate income. The analysis places the Sarong Index in the larger context of human-centred development paradigm and discusses its usefulness as a locally-based substitute of the traditional measures that promote the adoption of Maqasid Shariah compliance. The argument is supported by aligning the views of Ungku Aziz to the development trajectory in Malaysia after gaining independence, hence the Sarong Index, which would be a logical, though ethically conscious assessment, can be considered rational. The contribution will enhance the academic discourse on the inclusive development by demonstrating how the local or indigenous-based indicators and context-specific frameworks can support the mainstream development indicators in measuring the human welfare.